Return to Del - Rodda, Emily (Australia Scholastic Press, 2004)
Lief, Barda, and Jasmine have finally retrieved all the gems of the Belt of Deltora and now, in their final step towards overthrowing the Shadow Lord, they must find the true heir to the kingdom's throne.
Keywords: Magic -- Fantasy -- Magical thinking